2009
DOI: 10.1080/03605300902963500
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Planar Waves in the Allen–Cahn Equation

Abstract: We study the asymptotic stability of planar waves for the Allen-Cahn equation on n , where n ≥ 2. Our first result states that planar waves are asymptotically stable under any-possibly large-initial perturbations that decay at space infinity. Our second result states that the planar waves are asymptotically stable under almost periodic perturbations. More precisely, the perturbed solution converges to a planar wave as t → . The convergence is uniform in n . Lastly, the existence of a solution that oscillates p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 8 publications
2
66
0
Order By: Relevance
“…This is similar to that of [7], and therefore we omit it here. Theorem 1.2 and Proposition 1.1 can be proved by constructing the suitable upper and lower solutions, which are similar to those of [7]. We omit the details here.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…This is similar to that of [7], and therefore we omit it here. Theorem 1.2 and Proposition 1.1 can be proved by constructing the suitable upper and lower solutions, which are similar to those of [7]. We omit the details here.…”
Section: Introductionmentioning
confidence: 76%
“…Similar to [7], we have the following proposition, which shows that the convergence rate (1.7) is optimal in some sense. Proposition 1.1.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…One interesting avenue of future work is to investigate the multidimensional stability of planar traveling waves for equation (1.1) under weaker assumptions for the perturbations. For example, in the local case, Matano et al have recently shown that [15] the multidimensional stability of planar traveling waves with possibly large initial perturbations that only decay at space infinity. It would be interesting to see if their techniques can adapted to our nonlocal setting.…”
Section: Discussionmentioning
confidence: 99%